2016
DOI: 10.1111/trf.13615
|View full text |Cite
|
Sign up to set email alerts
|

Major transfusions remain frequent despite the generalized use of tranexamic acid: an audit of 3322 patients undergoing cardiac surgery

Abstract: Despite the use of tranexamic acid, 23% of cardiac surgery patients require a major transfusion. We identified predictors of major transfusion and showed that major transfusion is associated with important increases in mortality and morbidity. We conclude that there is still a need for an effective and safe blood-sparing drug in cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…Predictors of blood transfusion in our analyses were similar to the TRACS trial, which showed higher transfusion rates in patients with previous cardiac surgery (OR = 8.92; p = 0.04), longer duration of cardiopulmonary bypass (OR = 1.01; p = 0.03) and lower preoperative hemoglobin levels (OR = 0.51; p = 0.001), 9 and to Stevens et al, 17 who reported as predictors: CKD, previous cardiac surgery, urgency surgery, ejection fraction, type of surgery, CPB duration, age and low body mass index, although the last two was not confirmed in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Predictors of blood transfusion in our analyses were similar to the TRACS trial, which showed higher transfusion rates in patients with previous cardiac surgery (OR = 8.92; p = 0.04), longer duration of cardiopulmonary bypass (OR = 1.01; p = 0.03) and lower preoperative hemoglobin levels (OR = 0.51; p = 0.001), 9 and to Stevens et al, 17 who reported as predictors: CKD, previous cardiac surgery, urgency surgery, ejection fraction, type of surgery, CPB duration, age and low body mass index, although the last two was not confirmed in our study.…”
Section: Discussionsupporting
confidence: 85%